2014
DOI: 10.1016/j.evalprogplan.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation methods, implementation fidelity results and relationship to physical activity and healthy eating in the Faith, Activity, and Nutrition (FAN) study

Abstract: Faith, Activity and Nutrition (FAN), a community-based participatory research project in African American churches, aimed to increase congregant physical activity and healthy eating. The Health-Promoting Church framework, developed collaboratively with faith-based partners, guided the intervention and a comprehensive process evaluation. The Health-Promoting Church components related to healthy eating and physical activity were getting the message out, opportunities, pastor support, and organizational policy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 48 publications
3
31
0
1
Order By: Relevance
“…As the awareness of the importance of safety has continued to grow, system safety engineering has become a mature discipline and has gradually been extended to the aviation, nuclear, petroleum, chemical, and general manufacturing industries. Many theories and methods have been proposed, such as safety checklists [1], safety analysis [2] and evaluation methods [3], event trees (ETs) [4], fault tree analysis (FTA) [5] and risk assessment techniques [6], mode evaluation, human factor analysis and classification system (HFACS) applied on UK rail safety [7], six-stage safety and other risk index evaluation methods, and artificial neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…As the awareness of the importance of safety has continued to grow, system safety engineering has become a mature discipline and has gradually been extended to the aviation, nuclear, petroleum, chemical, and general manufacturing industries. Many theories and methods have been proposed, such as safety checklists [1], safety analysis [2] and evaluation methods [3], event trees (ETs) [4], fault tree analysis (FTA) [5] and risk assessment techniques [6], mode evaluation, human factor analysis and classification system (HFACS) applied on UK rail safety [7], six-stage safety and other risk index evaluation methods, and artificial neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent evaluation illuminated the concept that program execution was related to perceptions about aptitude and patronage, which was linked with exercise (Saunders, Wilcox, Baruth, & Dowda, 2014). In their discussion, the authors noted that "organizational level" adjustments can be quite cumbersome to attain and more work may be necessary to successfully integrate similar programs into the faith-based community (Saunders, Wilcox, Baruth, & Dowda, 2014).…”
Section: Program Effectiveness In Faith-based Settingsmentioning
confidence: 99%
“…Similarly, the "Faith, Activity, and Nutrition" program evaluated a faith-based intervention based on nutrition and exercise (Saunders, Wilcox, Baruth, & Dowda, 2014). The key objective was to complete a thorough evaluation of: program execution, censoring strategies, and techniques used to gauge program execution at the administrative stage (Saunders, Wilcox, Baruth, & Dowda, 2014). Their evaluation revealed that there was no observed surge in isometrics following program execution, nor was there any impact on diet (Saunders, Wilcox, Baruth, & Dowda, 2014).…”
Section: Program Effectiveness In Faith-based Settingsmentioning
confidence: 99%
See 2 more Smart Citations